Chapter 1 Civic Space-and Desire-Deranged From Le Corbusier to Georges Perec - Doel, Marcus A. (Taylor & Francis, 2019)
Civic Spaces and Desire presents an original and critical appraisal of civic spaces for a novel theoretical intersection of architecture and human geography. The authors address civic spaces that embody a strong moral code, such as a remembrance park or a casino, in various places in the United Kingdom, Europe, North America, Australia and Asia. The consecutive chapters of the book present these chosen spaces as the interconnection between the everyday and the ideological. By doing so the book reimagines the socio-political effects of the countercultural assemblages and ontologies of difference that these spaces produce, represent and foster, as presented through outcasts and nomads of various kinds and forms. The book reflects on different interpretations of the key texts from primarily post-linguistic theoreticians, such as Gilles Deleuze, Félix Guattari and Jacques Derrida. It will benefit students and academics in architecture, geography, philosophy and urban studies and planning, who seek to understand the politics of space, place and civility. By deconstructing normative ideological constructs, the book uses the concept of desire to explore the tensions between expectations of civic spaces and the disappointment and wonder of their immanent existence.